Analisis Usaha dan Pemasaran Pembenihan Udang Windu (Penaeus monodon) di HSRT Windu Tirta Samudra Desa Tanjung Limau Kecamatan Muara Badak - Olvhy Evelyne Mangampa; Qoriah Saleha; Juliani Juliani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Tiger shrimp farming is an aquaculture business associated with the rearing of shrimp from egg hatching until they are ready to be harvested for consumption. The amount of tiger shrimp production is highly dependent on the tiger shrimp hatchery process. This study was conducted with the aim to 1) Calculate the income of tiger shrimp hatchery business, 2) Analyze the feasibility of tiger shrimp hatchery business based on the criteria of Revenue Cost Ratio (RCR), Break Even Point (BEP), Payback Period, Return On Investman (ROI), and 3) Describe marketing channels, marketing margins, and farmer share in shrimp hatchery business. The sample method used was purposive sampling and snowball sampling. The results showed that tiger shrimp hatcheries in HSRT Windu Tirta Samudra earned an income of Rp.43,313,992/month. Based on the criteria of RCR, BEP, ROI and Payback Period (PP) tiger shrimp hatchery business is feasible to continue and run. Marketing of tiger shrimp seed forms level 0 and level 1 marketing channels, with a margin of Rp.2/head on level 1 marketing channels, and the farmer's share obtained is efficient because it is above 60%.